City Life, Farm Life - Wendy Graham (Oxford, United Kingdom Capstone Global Library Ltd, 2013)
Engage Literacy is the new reading scheme from Raintree that introduces engaging and contemporary content to motivate and support early readers while providing a reliable and instructional framework. All titles are precisely levelled, with new vocabulary being introduced and reinforced throughout the levels. This is a level 25 non-fiction title in the Lime book band level
Keywords: PY-UOI - Where we are in Place and Time -- PY-UOI - Where we are in Place and Time; Places